Blood and money [videorecording (DVD)] - Barr, John, 1972-; Berenger, Tom, 1949-; Hager, Kristen, 1984-; Ben-Victor, Paul; McDermott, Erica (Screen Media Films, 2020)
A retired veteran hunting in the Allagash backcountry discovers a dead woman with a duffle bag full of money. He soon finds himself in a web of deceit and murder.